Reflection-refraction coefficients and energy ratios in couple stress micropolar thermoviscous elastic solid - Kumar Sahrawat, Ravinder; Poonam (Zielona Góra: Uniwersytet Zielonogórski)
The reflection and refraction phenomenon of propagation of waves in couple stress micropolar thermoviscous elastic solid media with independent viscoelastic and micropolar properties have been studied. The structure of the model has been taken such that the plane interface is divides the given media into two half spaces in perfect contact.
Keywords: micropolar; thermoviscous; phase speed; energy ratio; reflection coefficient; refraction coefficient; couple stress